2007
DOI: 10.7202/032929ar
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary History of Cumberland Sound, Southeastern Baffin Island: The Marine Evidence

Abstract: ABSTRACTAcoustic and core data from Cumberland Sound show that glacial ice derived from the Foxe Sector (Amadjuak Dome) of the Laurentide Ice Sheet advanced to the continental shelf at the mouth of the sound during a late phase of the Foxe Glaciation. The basal lithofacies/acoustic unit (Ai/BUD) in the sound is a massive, black diamicton. On the basis of strati-graphic, acoustic, lithologie and faunal evidence, this unit is interpreted as till. The till is overlain by an ice pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 55 publications
7
34
0
Order By: Relevance
“…In their updated inventory, Margold et al (2015) also used the International Bathymetric Chart of the Arctic Ocean (IBCAO: Jakobsson et al, 2000) and more detailed swath bathymetry data from the Canadian Arctic (ArcticNet, 2013) to identify several new ice streams and confirm others that were previously hypothesised based only on terrestrial evidence. These bathymetric data have also been complemented by sub-surface data obtained from seismic reflection surveys, allowing workers to identify multiple till units, grounding zone wedges and other glacial features buried in the marine sediments; and to investigate the architecture of large trough mouth fans that often lie distal to the major ice stream troughs (Jennings, 1993;Andrews et al, 1995b;Rashid and Piper, 2007;Li et al, 2011;Siegel et al, 2012;Batchelor et al, 2013a,b;.…”
Section: Historical Perspective On Ice Streams In the Lismentioning
confidence: 98%
“…In their updated inventory, Margold et al (2015) also used the International Bathymetric Chart of the Arctic Ocean (IBCAO: Jakobsson et al, 2000) and more detailed swath bathymetry data from the Canadian Arctic (ArcticNet, 2013) to identify several new ice streams and confirm others that were previously hypothesised based only on terrestrial evidence. These bathymetric data have also been complemented by sub-surface data obtained from seismic reflection surveys, allowing workers to identify multiple till units, grounding zone wedges and other glacial features buried in the marine sediments; and to investigate the architecture of large trough mouth fans that often lie distal to the major ice stream troughs (Jennings, 1993;Andrews et al, 1995b;Rashid and Piper, 2007;Li et al, 2011;Siegel et al, 2012;Batchelor et al, 2013a,b;.…”
Section: Historical Perspective On Ice Streams In the Lismentioning
confidence: 98%
“…Cumberland Sound hosted one of the ice-shelves for the NE part of the LIS, and it is known to have been occupied by grounded glacial ice-sheet at least until the YD (Jennings, 1993). Erosion of Cretaceous black shale has resulted in the accumulation of dark-color sediments (Jennings, 1993).…”
Section: Timing Of Cumberland Sound Ice-shelf and Hudson Strait Icestmentioning
confidence: 99%
“…To the north, sedimentological studies and high-resolution AMS dating of marine sediment cores from the SE Baffin and Labrador shelves, and adjacent slopes, led to a reconsideration of LLGM ice extent in that region (Dyke et al, 2002). Jennings (1993), for example, concluded that Cumberland Sound was filled by an ice stream until ~11.5 ka (~10 14 C ka) which Kaplan (1999) suggested may have extended onto the continental shelf (see also Miller et al, 2002). In northern Labrador, Clark and Josenhans (1990) combined marine and terrestrial evidence to suggest that LGM ice was more extensive than previously mapped, with the ice limit extending onto the continental shelf.…”
Section: Extent and Thickness Of The Lis At Its Local Last Glacial Mamentioning
confidence: 99%